Households’ participation in community based organisations’ poverty reduction programmes in Oyo state Nigeria (1999 – 2012) (2014)
Community-Based Organisations (CBOs) are known to contribute to development especially at the grassroot level. However, the contribution of households in CBOs’ poverty alleviation has not been given adequate attention in the literature. This study, therefore, examined households’ level of participation in CBOs’ poverty reduction programmes in Oyo State, which has the highest number of CBOs’ in Southwestern Nigeria. Arnstein’s Ladder of Citizen Participation provided the analytical framework within a cross-sectional survey research design. A multi-stage sampling procedure was used to select 10 (29.0%) local government areas from the three Senatorial districts: four in Oyo North (ON), three in Oyo Central (OC) and three in Oyo South (OS). A structured questionnaire focusing on level of household participation in community development (citizen power, tokenism, and non-participation), factors responsible for poverty reduction and challenges to participation was administered to 1,104 randomly selected household heads (399 in ON, 308 in OC and 397 in OS). In-depth interviews were conducted with members of randomly selected CBOs in each of the senatorial districts to obtain information on the projects executed and level of households’ involvement. Qualitative data were content analysed, while quantitative data were analysed using descriptive statistics and ANOVA at 0.05 level of significance. Citizen power (54.8% in ON, 37.2% in OC and 50.5% in OS), tokenism (21.2% in ON, 27.8% in OC and 21.9% in OS) and non-participation (23.9% in ON, 35.0 % in OC and 27.6% in OS) were observed levels of participation. Mean incidence of poverty reduced from 5.3 to 1.4 in ON, 6.8 to 2.3 in OC and 3.9 to 1.1 in OS over time. This reduction was attributed to salary increase (9.0% in ON, 6.9% in OC and 8.9% in OS), birth control (13.8% in ON, 10.6% in OC and 13.7% in OS) and multiple jobs by the heads of household (15.1% in ON, 4.7% in OC and 12.8% in OS). The mean values of challenges to participation in development were financial problems (4.8±0.1 in ON, 3.6±0.4 in OC and 3.7±0.2 in OS), disparity in wealth (4.4±0.6 in ON, 3.6±0.2 in OC and 3.8±0.2 in OS) and power relations among community members (4.3±0.2 in ON, 3.5±0.5 in OC and 3.3±0.1 in OS). Development projects implemented by the CBOs were 38.8% in ON, 35.0% in OC and 26.2% in OS. Provision of infrastructural facilities by CBOs were 55.3% in ON, 72.1% in OC and 65.1% in OS; while economic and empowerment projects were 20.3% in ON, 8.1% in OC and 9.6% in OS. Security projects were 24.4% in ON, 19.8% in OC and 25.3% in OS. There was no significant difference in households’ levels of involvement in CBOs’ poverty alleviation programmes among the senatorial districts (F=0.13). Males were two times involved in CBOs’ poverty alleviation programmes than females in all the Senatorial districts. In spite of several benefits derived from Community-Based Organisations’ poverty alleviation programmes, households’ involvement in Oyo State was low. Households’ involvement should be strengthened by the government at different levels.